Keterkaitan antara Faktor Lingkungan Hidro Oseanografi dengan Komunitas Gastropoda pada Kondisi Mangrove Berbeda di Kabupaten Kepulauan Selayar - Abbas, Ahmad Ashar; Lapong, Muh. Imran; Noor, Rahmat Januar; Fathuddin (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2024)
A study of the mangrove ecosystem, gastropod community structure, and the influence of hydrooceanography at three district station points on Selayar Island was carried out from March to April 2017. This research aims to show mangrove density in various conditions, to reveal the structure of the gastropod community. and the influence of hydrooceanography. This research was analyzed using the Shannon Wiener index variation method and The Principle Component Analysis (PCA). Overall research findings show: 1) mangrove density values at three station points, namely: a) station 1 (0.35); b) station 2; and c) station 3 (0.16); 2) gastropod density values, namely: a) station 1 (3.44); b) station 2 (3.00); c) station 3 (2.81). The highest relative and absolute frequency value of all stations is Littorina Scabra and the lowest is Terrebralia Pallustris. The diversity index value for gastropod species at various stations ranges from 1.00 to 1.45 and the unity index value ranges from 0.25 to 0.31, which is still relatively low. The distribution pattern of gastropods classified as community groups at each station ranged between 2.53-8.53. The results of the Principle Component Analysis show that gastropods at each station are influenced by environmental factors (Hydro Oceanography).